Sor Tommasa Fieschi (1448-1534). The first woman who commented Dionisio Areopagita - Pico Estrada, Paula (Itinerari, 2023)
The essay aims to introduce Sister Tommasina Fieschi’s (1448-1534) commentaries on the letters of Dionysius the Areopagite, the first known commentary on his work written by a woman. To this end, first I introduce Sister Tommasina, her writings, and the existing editions of her work. Secondly, I contextualize Tommasina’s commentary in the affective dionysian tradition where it belongs. Finally, I analyze some passages of her commentary on Dionysius’Epistle V in order to show the uniqueness of her interpretation of the expresion “divina caligo”.